2018
DOI: 10.1007/s12035-018-1298-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Neuroplasticity, Cardiovascular, and Cognitive-Associated Genomic Variants in Familial Alzheimer’s Disease

Abstract: The identification of novel genetic variants contributing to the widespread in the age of onset (AOO) of Alzheimer's disease (AD) could aid in the prognosis and/or development of new therapeutic strategies focused on early interventions. We recruited 78 individuals with AD from the Paisa genetic isolate in Antioquia, Colombia. These individuals belong to the world largest multigenerational and extended pedigree segregating AD as a consequence of a dominant fully penetrant mutation in the PSEN1 gene and exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…LOXL4 ECM induced plasticity as well as induction of proliferative activity could lead to a better physiological stability of PSEN1-mutated cells, which results in the ADAOO delaying effect observed in these patients. This effect is in line with the delayer effect of the APOE*E2 allele in this cohort [5,35]. Given the biological relatedness between APOE and LOXL4( Table 3), the synergistic effect of these two genes on ADAOO is yet to be elucidated.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…LOXL4 ECM induced plasticity as well as induction of proliferative activity could lead to a better physiological stability of PSEN1-mutated cells, which results in the ADAOO delaying effect observed in these patients. This effect is in line with the delayer effect of the APOE*E2 allele in this cohort [5,35]. Given the biological relatedness between APOE and LOXL4( Table 3), the synergistic effect of these two genes on ADAOO is yet to be elucidated.…”
Section: Discussionsupporting
confidence: 78%
“…Individuals included in this study exhibit an extreme phenotype, that is, suffer from AD caused by the PSEN1 E280A fully penetrant mutation, belong to the Paisa genetic isolate and their AD age of onset (ADAOO) ranges from the early 30s to the late 70s [23]. In previous studies [3,5,7,35], we successfully applied this sampling strategy using extreme phenotypes (of major effect phenotypes) [36][37][38][39]. Power estimates are included in the Supplementary Material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with astrotactin 1, astrotactin 2 plays a key role in glial‐guided neuronal migration during development of the laminar architecture of cortical regions of the mammalian brain 23,24 . Some researchers reported that certain variants of the ASTN2 gene might be associated with the development of neuropsychiatric disorders, such as autism spectrum disorder, attention‐deficit/hyperactivity disorder, anxiety, obsessive‐compulsive disorder, schizophrenia, and Alzheimer's disease, 25–27 although others did not find such associations between ASTN2 gene variants and neuropsychiatric disorders 28 . A substantial number of studies have shown or suggested interactions between these neuropsychiatric disorders and alterations of opioid system function 29–32 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to f AD, mutations in genes associated with s AD do not directly cause AD but confer susceptibility [ 28 ]. Although f AD and s AD forms are phenotypically similar, the age of onset (AOO) at which signs and/or symptoms of AD appear for the first time in cases of f AD is generally earlier than in cases of s AD, with important predictors of ADAOO in s AD correspond to several genetic variants of small effect [ 29 , 30 ]. Indeed, it is generally established that f AD cases have an AOO before 65 years (ranging from the early 30s to the late 70s), while the AOO in s AD generally starts after 65 years [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%